Computational materials engineering : achieving high accuracy and efficiency in metals processing simulations /: achieving high accuracy and efficiency in metals processing simulations. (2015) - Pietrzyk, Maciej, 1947-; Madej, Łukasz; Rauch, Lukasz; Szeliga, Danuta
No abstract available